Analisis Perbandingan Pelayanan Bank Syariah Dan Bank Konvensional - Nikmatus Zakiyah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2020)
This study discusses to study and discuss about Islamic banking services and conventional bank services. This journal uses the method of library research that is research whose source of information and references from various library materials by reading and studying books and writings that have objects with this discussion. According to the results of the study found Can be known about the services received by Islamic banks better than conventional banks because of the age side, Islamic banks are far from conventional banks. Sharia banks which incidentally are basic sharia banks, provide services of better quality than conventional banks.